2001
DOI: 10.1191/096120301701548463
|View full text |Cite
|
Sign up to set email alerts
|

Lupus patients are protected from cancer

G RV Hughes

Abstract: The title of this short editorial is deliberately provocative. The fact is that, perhaps surprisingly, there are no major, or even remotely definitive studies of the subject. The article in this issue of Lupus by Xu and Wiernik 1 provides a thoughtful review hinting at a positive rather than a negative association between the two diseases.Yet in the experience of this physician with 30 years' lupus practice, and currently with 2500 lupus patients on the clinic register, the association between lupus and cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1

Year Published

2002
2002
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 5 publications
0
11
1
Order By: Relevance
“…Although the point estimates of several of the studies support an increased risk of malignancy in lupus, the wide CIs (which include the null value in 50% of the studies) make it impossible to draw a definitive conclusion. A recent editorial by a leading researcher of lupus, based on anecdotal experience, argues that the risk of malignancy may be decreased in SLE [45].…”
Section: Table 1 Potential Links Between Systemic Lupus Erythematosumentioning
confidence: 99%
“…Although the point estimates of several of the studies support an increased risk of malignancy in lupus, the wide CIs (which include the null value in 50% of the studies) make it impossible to draw a definitive conclusion. A recent editorial by a leading researcher of lupus, based on anecdotal experience, argues that the risk of malignancy may be decreased in SLE [45].…”
Section: Table 1 Potential Links Between Systemic Lupus Erythematosumentioning
confidence: 99%
“…The long-term exposure of patients suffering from these disorders to immunosuppressive therapy may have confounded the association with cancer. On the other hand, it has been suggested that the autoimmune 'haplotype' [14] protects against infections and malignancy. MS is a putative autoimmune disease affecting the central white matter and results in progressive neurological disability over time.…”
Section: Introductionmentioning
confidence: 98%
“…teraction between cancer and autoimmunity is not yet fully understood [14,15]. On the one hand, there are studies suggesting a protective effect of autoimmunity against cancer [7,[14][15][16][17][18][19], on the other hand, several studies have indicated an increased cancer risk of autoimmune disease. However, in these latter studies, particularly malignant lymphoproliferative diseases seem to be increased [7], which might be a consequence of either chronic antigenic hyperstimulation or viral reactivation under long-term immunosuppressive treatment.…”
Section: Discussionmentioning
confidence: 99%